Digital Learning Factory for Developing 21st-Century Competencies in Physics Teacher Education toward SDG 4 - Dwi Pangga; Kadek Rihendra Dantes; Dewa Gede Hendra Divayana; Ketut Suma; Wayan Suastra; Putu Artawan (Journal of Innovative Technology and Sustainability Education, 2026)
Objective: This study aims to conduct a Systematic Literature Review (SLR) on the implementation of the Learning Factory (LF) model in physics education, particularly for the development of 21st-century competencies among preservice physics teachers. Method: Using the PRISMA framework, the review analyzed literature published between 2020 and 2025. Articles were identified using Publish or Perish software with Google Scholar as the primary database. A total of 32 relevant journal articles were systematically screened, extracted, and synthesized using thematic narrative analysis. Results: The review reveals that the Learning Factory (LF) is a promising instructional approach that effectively integrates theory and practice through project-based and experiential learning in simulated real-world environments. LF enhances critical thinking, creativity, collaboration, communication, and digital literacy, which are core competencies in 21st-century education. However, its implementation in teacher education still faces several challenges, including limited infrastructure, lack of faculty training, and misalignment in assessment systems. Novelty: This study contributes by systematically mapping the role of the Learning Factory model in physics teacher education, which remains relatively underexplored in existing research. The findings highlight LF’s strategic potential to bridge the gap between theory and practice and provide recommendations for curriculum design, faculty development, and institutional collaboration.